Histone Deacetylase Inhibitors Protect Against Pyruvate Dehydrogenase Dysfunction in Huntington's Disease - Naia, Luana (2017)
Transcriptional deregulation and changes in mitochondrial bioenergetics, including pyruvate dehydrogenase (PDH) dysfunction, have been described in Huntington's disease (HD). We showed previously that the histone deacetylase inhibitors (HDACIs) trichostatin A and sodium butyrate (SB) ameliorate mitochondrial function in cells expressing mutant huntingtin. In this work, we investigated the effect of HDACIs on the regulation of PDH activity in striatal cells derived from HD knock-in mice and YAC128 mice. Mutant cells exhibited decreased PDH activity and increased PDH E1alpha phosphorylation/inactivation, accompanied by enhanced protein levels of PDH kinases 1 and 3 (PDK1 and PDK3). Exposure to dichloroacetate, an inhibitor of PDKs, increased mitochondrial respiration and decreased production of reactive oxygen species in mutant cells, emphasizing PDH as an interesting therapeutic target in HD. Treatment with SB and sodium phenylbutyrate, another HDACI, recovered cell viability and overall mitochondrial metabolism in mutant cells. Exposure to SB also suppressed hypoxia-inducible factor-1 (HIF-1α) stabilization and decreased the transcription of the two most abundant PDK isoforms, PDK2 and PDK3, culminating in increased PDH activation in mutant cells. Concordantly, PDK3 knockdown improved mitochondrial function, emphasizing the role of PDK3 inactivation on the positive effects achieved by SB treatment. YAC128 mouse brain presented higher mRNA levels of PDK1-3 and PDH phosphorylation and decreased energy levels that were significantly ameliorated after SB treatment. Furthermore, enhanced motor learning and coordination were observed in SB-treated YAC128 mice. These results suggest that HDACIs, particularly SB, promote the activity of PDH in the HD brain, helping to counteract HD-related deficits in mitochondrial bioenergetics and motor function.SIGNIFICANCE STATEMENT The present work provides a better understanding of mitochondrial dysfunction in Huntington's disease (HD) by showing that the pyruvate dehydrogenase (PDH) complex is a promising therapeutic target. In particular, the histone deacetylase inhibitor sodium butyrate (SB) may indirectly (through reduced hypoxia-inducible factor 1 alpha stabilization) decrease the expression of the most abundant PDH kinase isoforms (e.g., PDK3), ameliorating PDH activity and mitochondrial metabolism and further affecting motor behavior in HD mice, thus constituting a promising agent for HD neuroprotective treatment.